2014
DOI: 10.1542/peds.2013-2823
|View full text |Cite
|
Sign up to set email alerts
|

Supplemental Nutrition Assistance Program Participation and Child Food Security

Abstract: WHAT'S KNOWN ON THIS SUBJECT: Recent studies have shown that participating in the Supplemental Nutrition Assistance Program (SNAP) is associated with improved household food security. With the exception of 1 descriptive analysis, studies have not examined how SNAP affects children' s food security. WHAT THIS STUDY ADDS:This article estimates the association between SNAP and children' s food security using the largest, most rigorous national study of food security to date. Given current proposals to reduce prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
85
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(93 citation statements)
references
References 37 publications
6
85
1
1
Order By: Relevance
“…Federal benefits can attenuate the severity of food insecurity but might not eliminate it, particularly for children and in regions with higher food costs. 15,16 …”
Section: Introductionmentioning
confidence: 99%
“…Federal benefits can attenuate the severity of food insecurity but might not eliminate it, particularly for children and in regions with higher food costs. 15,16 …”
Section: Introductionmentioning
confidence: 99%
“…To identify the probability of immediate reemployment, we assume it is the same as the job finding probability of other unemployed workers. In addition, we calibrate the probability of transitioning from long-term unemployment to employment based on the finding of Mabli, Tordella, Castner, Godfrey, and Foran (2011) that 3% of SNAP participants leave the program each month. Our procedure is as follows: we use the moments above to create a target transition matrix across employment states that our model should generate.…”
mentioning
confidence: 99%
“…This finding may initially seem counterintuitive, but is in fact a natural consequence of the fact that the programme and others like it are reaching families with the greatest need. However, as noted above, carefully constructed empirical designs that take advantage of natural experiments to address selection have found that participation in SNAP and other programmes is associated with decreased food insecurity (2)(3)(4)(5)(6) . In this sense, the use of geographic accessibility as a proxy for participation is a boon, since it is far less likely that families with high levels of need (food insecurity) choose where to live because of proximity to a summer meals site.…”
Section: Addressing Selection Biasmentioning
confidence: 99%
“…In 2013, the fifteen domestic food and nutrition assistance programmes administered by the USDA reached about 25 % of Americans at a cost of nearly $US 109 billion (1) . Studies of the largest of these programmes (including the Supplemental Nutrition Assistance Program (SNAP) and the Special Supplemental Nutrition Program for Women, Infants, and Children (WIC)) have most frequently found that they are successful in reducing both household and child food insecurity (2)(3)(4)(5)(6) . However, much less is known about how other nutrition programmes impact household food security.…”
mentioning
confidence: 99%